2023
DOI: 10.55047/jhssb.v3i1.845
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Innovation on the Relationship Between Supply Chain Management and Company Performance in the Kingdom of Bahrain

Tariq Tawfeeq Yousif Alabdullah,
Abdulkarim Kanaan-Jebna

Abstract: This research focuses on critical independent variables, including information quantity and quality sharing, and the adoption of lean practices within companies. It examines these variables to understand their effects on corporate performance using innovation as a mediator. Data from registered non-financial businesses in Bahrain are utilized, and Smart PLS is recommended for analysis. The study aims to unravel the intricate relationships among these variables in Bahrain's nonfinancial sector. Conceptually, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Then, this study also found that consistent product quality is an important element in maintaining competitiveness. Fast product delivery and quality are two important elements considered by consumers in buying and using product and service that provided by companies [10,13]. Furthermore, this study also found that sales growth is an important element in measuring business performance [8,14].…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Then, this study also found that consistent product quality is an important element in maintaining competitiveness. Fast product delivery and quality are two important elements considered by consumers in buying and using product and service that provided by companies [10,13]. Furthermore, this study also found that sales growth is an important element in measuring business performance [8,14].…”
Section: Resultssupporting
confidence: 51%
“…Generally, company performance can be measured from financial and nonfinancial aspects. Financial aspect includes profit, and return on investment, while nonfinancial aspects comprise sales growth, market share, employee productivity, and customer satisfaction [9,10]. Based on theoretical and empirical studies, then the purpose of this study is to identify and explain the important elements that affect variable of supply chain strategy, competitiveness, and business performance in the context of passion fruit processing industry.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of regional autonomy has spurred the development of public sector accounting. Similarly, during the New Order regime, fiscal decentralization was enacted, compelling each local government to enhance its accounting system and regional financial management [4]. This improvement is critical to meet the demands for transparent government public accountability regarding the use of public funds.…”
Section: Introductionmentioning
confidence: 99%